From the aesthetic experience to the aesthetic commentary of a musical work (Islas, 2024)
Introduction: The dissolution of the object of study of aesthetics within the most current aesthetic commentaries in the arts is addressed, and the necessary rescue of the emotional component in music is grounded in its close relationship with the notion of aesthetic experience.Methods: The article responds to a process of academic experimentation based on the critical and essayistic experience of the authors, observation, comparison, and evaluation of referential sources, and critically grounded theoretical-methodological production.Results: An evaluation of the current state of aesthetic commentary in the field of music in its general artistic context is provided, along with a model that redirects academic exercise from the disciplinary object of aesthetics, useful in elementary and higher musical training processes.Conclusions: Aesthetic commentary in the arts (and especially in music, as the most subjective and emotional manifestation) has undergone alterations that hinder the apprehension of the disciplinary object of study, justifying new proposals and actions in academia.
Keywords: music; aesthetics; aesthetic experience; musical aesthetic commentary